Potential of Mango Leaf Methanol Extract (Mangifera indica L.) as A Bioherbicide Against The Growth of Putri Malu Weed (Mimosa pudica L.) - Adellya Nabilla Putrie; Zakiah, Zulfa; Mukarlina, Mukarlina (Jurnal Biologi Tropis, 2024)
Putri Malu (Mimosa pudica L.) is a weed that often found in various places, especially on agricultural land and plantations. Mangifera indica L. has potential as a bioherbicide because it contains aleochemical compounds, which inhibit the growth of other plants. This research aims to determine the potential and the best concentration of methanol extract of mango leaves (Mangifera indica L.) in inhibiting the growth of putrimalu weed (Mimosa pudica L.). This research was carried out for four months, in the Kasa House Laboratory, Biology Department, Faculty of Mathematics and Natural Sciences, Tanjungpura University. The research used a Completely Randomized Design (CRD) with five mango leaf extract concentration treatment levels, namely control (P0), 10% (P1), 20% (P2), 30% (P3), and 40% (P4). Each treatment was repeated five times to obtain 25 experimental units. The results showed that the methanol extract of mango leaves (Mangifera indica L.) had an effect on inhibiting the germination and growth of the M. pudica weed. The best concentration of methanol extract of mango leaves in inhibiting the germination and growth of putrimalu weed is a concentration of 20%.